2021
DOI: 10.1097/dcr.0000000000001964
|View full text |Cite
|
Sign up to set email alerts
|

Gracilis Muscle Interposition for Treatment of Complex Anal Fistula: Experience With 119 Consecutive Patients

Abstract: BACKGROUND: Treatment of complex anal fistula is challenging, often mandating multiple procedures. The gracilis muscle has been used to treat perineal fistulas and to repair perineal defects. OBJECTIVE: This study aims to report the results of gracilis muscle interposition for complex anal fistula, including prognostic factors for success. DESIGN: This is a retrospective analysis of a prospective database fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 14 publications
1
16
0
1
Order By: Relevance
“…The results show a primary healing rate of 33% and an overall healing rate of 65% when further intervention was indicated for final closure of the fistula. Similar results were obtained in previous studies [ 2 , 4 , 10 26 ]. Success rates in previous studies varied from 42 to 100% for primary healing by GMT alone and from 71 to 100% for overall healing (Table 5 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results show a primary healing rate of 33% and an overall healing rate of 65% when further intervention was indicated for final closure of the fistula. Similar results were obtained in previous studies [ 2 , 4 , 10 26 ]. Success rates in previous studies varied from 42 to 100% for primary healing by GMT alone and from 71 to 100% for overall healing (Table 5 ).…”
Section: Discussionsupporting
confidence: 93%
“…What almost all these studies have in common is the fact that a significant increase in the success rate was observed when further procedures were performed after GMT. This was shown particularly clearly in a recent study by Yellinek et al [ 26 ], which is also the largest series to date with a total of 119 patients. The percentage of successfully closed fistulas in the latter study increased from 42 to 92% after additional interventions.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Out of the 16 studies including details on previous repairs, only 4 studies included patients in whom GMI was the first treatment. 28,32,37,40 The interval between RVF development and GMI ranged between 0 to 5 years.…”
Section: Resultsmentioning
confidence: 99%
“…Apesar retovaginal com a simples derivação de trânsito é um evento incomum, mas também descrito em outras séries 61 . Fístulas retovaginais são de tratamento complexo e podem envolver retalhos regionais com índices de sucesso variáveis 62,63 , devendo ser indicado apenas para pacientes muito motivados e após período de tempo suficiente para determinar o prognóstico oncológico, apesar de não ter sido realizado em nenhum paciente desta série.…”
Section: Análise Estatísticaunclassified